Human resource management in Greece in comparative perspective: alternative institutionalist perspectives and empirical realities - Alexandros Psychogios; Geoffrey Wood (2010)
This paper seeks to understand the effects of institutions on the practice of human resource management (HRM) in Greece. Hence, it evaluates how alternative approaches to institutions conceptualize contexts such as Greece, and the relevance of such approaches in the light of empirical evidence. The latter would suggest that, in common with other Mediterranean economies, Greece has been undergoing a long evolution, marked by reforms both towards greater liberalization and greater coordination. However, the ultimate direction remains unclear, and embedded ways of doing things – above all, a strongly paternalist tradition – persist. Again, as with other Mediterranean economies, the Greek economy is an essentially dualistic one, divided between larger organizations (both within the state and private sectors) and the SME sector: the relative importance of the latter has increased in recent years. Empirical research evidence would underscore the importance of conceptualizing institutions as subject to both continuity, and uneven, contested, yet constant change, and the extent to which internal diversity persists within national institutional frameworks.